Edukasi Gizi Kesehatan Masyarakat Tentang Keanekaragaman Pangan Bagi Masyarakat di Kalurahan Argomulyo Kapanewon Cangkringan Kabupaten Sleman D.I Yogyakarta - Rini Pratiwi; Markus Gelar Kumara Agni; Nur Aini; Soepri Tjahjono Moedji Widodo; Nur Alvira Pasca Wati DP; Alfina Himatun Ulya; Muhammad Alvin Rusydi (Institut Nalanda, 2026)
Indonesia has abundant biological resources that support food diversity; however, community dietary patterns remain dominated by rice, limiting the utilization of local food resources and potentially affecting nutritional quality and household food security. Argomulyo Village, Cangkringan District, Sleman Regency, Special Region of Yogyakarta, has strong potential for food diversity due to its fertile volcanic soil and diverse agricultural activities. This community service program aims to increase public knowledge and awareness of the importance of consuming diverse, nutritious, balanced, and safe foods to improve nutritional status and household food security. The program is implemented through nutrition education, counseling, interactive discussions, and the distribution of educational materials on local food utilization. The target participants are residents of Argomulyo Village, particularly housewives and community health volunteers. Expected outcomes include improved community knowledge of food diversity, publication in an accredited national journal, and integration of program outcomes into the Community Intervention course. The program also supports Higher Education Key Performance Indicators (KPIs), including KPI 2, KPI 3, and KPI 5.